(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The objective of this research was to examine the association between 25-hydroxycalciferol status and disease activity in patients diagnosed with Systemic Lupus Erythematosus (SLE) and concurrent renal impairment. Additionally, the study aimed to evaluate the correlation of 25-hydroxycalciferol levels with clinical and laboratory data, exploring the possibility of utilizing them as biomarkers for assessing renal activity in individuals with lupus nephritis. A total of 128 participants were enrolled in the study and subsequently categorized into three distinct groups: group I (SLE active lupus nephritis group) which included 53 patients with SLE, and group II (SLE/inactive LN), which included 57 patients and group III, which included 30 practically healthy people from the control group. Patients were subjected to a complete history and clinical examination. All participants underwent standardized assessments, including SLEDAI-2K evaluation for disease activity and serum 25-hydroxycalciferol level measurements. Results: The findings of this study revealed a significant decrease in serum 25-hydroxycalciferol levels among patients diagnosed with SLE/LN when compared to the healthy control group. Furthermore, patients experiencing active lupus nephritis demonstrated even lower levels of 25-hydroxycalciferol. This suggests a higher prevalence of 25-hydroxycalciferol insufficiency and deficiency within the SLE/LN patient population, particularly during periods of active disease. A statistically significant association was identified between reduced serum 25-hydroxycalciferol levels and the presence of fatigue, photosensitivity, and hypertension. Regression analysis highlighted lupus nephritis, photosensitivity, and high blood pressure as the most influential factors affecting serum 25-hydroxycalciferol levels in individuals with SLE.